Wax Teeth and Metallic Superstructure Trials at the Same Session: Simplified Technique for Implant-Supported Prosthesis - Margonar, Rogerio; de Almeida, Erika Oliveira; Queiroz, Thallita Pereira; Marcantonio, Elcio [UNESP] (Lippincott Williams & Wilkins, 2010)
This clinical report describes a method to reduce the number of clinical sessions for the rehabilitation of implant-supported fixed dentures through a simplified and versatile procedure indicated mainly for immediate loading. According to this method, the immediate implant-supported fixed dentures for edentulous patients can be safely fabricated within 2 days. In this technique, the teeth in the wax are prepared on a base of light-polymerized resin, and both wax teeth and metallic superstructure trials are accomplished at the same session.
Keywords: Oral rehabilitation; prosthesis and implants; jaw; edentulous